2019
DOI: 10.3389/fpubh.2019.00242
|View full text |Cite
|
Sign up to set email alerts
|

Using Genomics to Track Global Antimicrobial Resistance

Abstract: The recent advancements in rapid and affordable DNA sequencing technologies have revolutionized diagnostic microbiology and microbial surveillance. The availability of bioinformatics tools and online accessible databases has been a prerequisite for this. We conducted a scientific literature review and here we present a description of examples of available tools and databases for antimicrobial resistance (AMR) detection and provide future perspectives and recommendations. At least 47 freely accessible bioinform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
293
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(302 citation statements)
references
References 95 publications
(75 reference statements)
3
293
1
5
Order By: Relevance
“…Especially, short‐read WGS has difficulties for managing direct repeats and plasmid analysis and can be misleading in investigating plasmid‐related AMR genes. Different databases/bioinformatic tools/nomenclature could hamper the comparative accuracy of the results. A comprehensive and curated catalogue of resistance mutations and genes has to be set up and agreed on, as well as the use of a harmonised computational approach to predict AMR from WGS data (Hendriksen et al., 2019a). Also, clear criteria to define a gene as ‘novel’ (i.e.…”
Section: Assessmentmentioning
confidence: 99%
“…Especially, short‐read WGS has difficulties for managing direct repeats and plasmid analysis and can be misleading in investigating plasmid‐related AMR genes. Different databases/bioinformatic tools/nomenclature could hamper the comparative accuracy of the results. A comprehensive and curated catalogue of resistance mutations and genes has to be set up and agreed on, as well as the use of a harmonised computational approach to predict AMR from WGS data (Hendriksen et al., 2019a). Also, clear criteria to define a gene as ‘novel’ (i.e.…”
Section: Assessmentmentioning
confidence: 99%
“…Presently, there are at least 47 bioinformatic resources/tools, but no a 'standard' pipeline has been developed speci cally to characterize the resistome. In this regard, the results are heavily dependent on the analysis methods (assembly-based or read-based) or reference database [34]. In this study, the ARG-OAP (v2) pipeline was applied, which uses a custom database with a hybrid UBLAST and BLASTX algorithm, re ecting the critical need for a comprehensive database combined with lower identity matching for antimicrobial resistance gene annotation of metagenomic data [35].…”
Section: Discussionmentioning
confidence: 99%
“…showed that the pFec10 plasmid does not encode genetic elements that mediate antibiotic resistance (Hendriksen et al, 2019). Plasmid stability is most likely maintained by the type II toxin-anti-toxin system YdeE-YdeD (Prevent host death-death on curing (Phd-Doc)), whereby ydeD encodes a "death on curing" toxin (Lehnherr et al, 1993;Liu et al, 2008).…”
Section: Assessment Of Characteristic Elements For Plasmid Maintenancementioning
confidence: 99%